Hydrogen Sulfide: A Potent Tool in Postharvest Fruit Biology and Possible Mechanism of Action - Ziogas, Vasileios; Molassiotis, Athanassios; Fotopoulos, Vasileios; Tanou, Georgia (Frontiers in Plant Science, 2018)
Hydrogen sulfide (H2S), an endogenous gaseous molecule, is considered as a signaling molecule, alongside small reactive compounds such as hydrogen peroxide (H2O2) and nitric oxide (NO), in various plant systems. Recently, accumulating evidence has shown that postharvest application of H2S through the use of H2S donors, can inhibit fruit ripening and senescence programs in numerous fruits. The focus of this mini-review is to summarize the impact of H2S action in postharvest physiology of several climacteric and non-climacteric fruit, such as banana, apple, pear, kiwifruit, strawberry, mulberry fruit and grape. In addition, we highlight several candidate mechanisms, including a putative cross-talk between H2S and ethylene, reactive oxygen and nitrogen species and oxidative/nitrosative stress signaling, posttranslational modification of protein cysteine residues (S-sulfhydration), and energy metabolism-related responses as being functional in this H2S postharvest action. Since most of the fleshy fruit are susceptible to senescence, the prevention of postharvest losses via H2S application will continue to be one of the priorities of horticultural research in the future. Understanding H2S metabolism and signaling during postharvest storage and the interplay with other key player molecules would therefore provide new, improved strategies for better fruit postharvest storage.